Analysis of Success and Barriers to Implementing Health Service Management Information Systems in Indonesia: Case Studies and Recent Literature Review - Samura, Jul Asdar Putra (JURNAL KESMAS DAN GIZI (JKG), 2025)
Digital transformation in healthcare services in Indonesia has encouraged the use of Hospital Management Information Systems (SIMRS) as a crucial instrument for improving service quality, efficiency, and accountability. However, its implementation still faces various technical and non-technical obstacles. This study employed a systematic literature review approach by analyzing ten Google Scholar-indexed articles published between 2022 and 2025. Articles were selected using the keywords "SIMRS," "health management information system," and "health service implementation." Data were analyzed to identify the objectives, benefits, obstacles, and strategies for SIMRS implementation in Indonesia. The review results indicate that SIMRS can improve administrative efficiency, accelerate patient data access, strengthen inter-unit coordination, and improve the accuracy of pharmaceutical services. Determining factors for success include system quality, management support, and government regulations. Obstacles identified include limited infrastructure, low digital literacy among healthcare workers, resistance to change, budget constraints, and poor interoperability between systems. The combined analysis confirms that the success of SIMRS implementation is influenced not only by technological aspects, but also by human resource readiness, managerial support, and government policies. Key challenges recurrent in the literature highlight the need for a holistic approach to strengthening human resource capacity, equitable digital infrastructure, standardizing interoperability, and providing sustainable financing. The implementation of SIMRS in Indonesia has significant potential to improve the quality of healthcare services, but its success depends on an integrated strategy that integrates technology, human resources, management, and regulations. Key recommendations include strengthening digital literacy, investing in infrastructure, establishing national interoperability standards, and fostering multi-stakeholder collaboration to ensure effective, inclusive, and sustainable digitalization of healthcare services.